Evaluation and comparison of the microhardness of enamel after bleaching with fluoride free and fluoride containing carbamide peroxide bleaching agents and post bleaching anticay application: An in vitro study - Liza George; Allu Baby; T Prasanth Dhanapal; K M Charlie; Asha Joseph; Anjum Anna Varghese (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: The purpose of the study was to evaluate and compare the microhardness of enamel after the application of anticay on bleached enamel with fluoride containing and fluoride free bleaching agent. Materials and Methods: Twenty freshly extracted teeth decoronated and divided mesiodistally into two halves were randomly divided into five groups with 10 samples in each group. The enamel surface was treated as follows: Group 1 - no treatment, Group 2 - fluoride free bleaching agent, Group 3 - fluoride containing bleaching agent, and Group 4 - fluoride free bleaching agent followed by anticay application. The samples were subjected to indentation to test the microhardness using Vicker's hardness analyzer. Conclusion: Enamel microhardness significantly increased in samples where anticay was used after the application of bleaching agent.